Comparison of Real-Time PCR and FTIR with Chemometrics Technique in Analysing Halal Supplement Capsules - Mohd Sukri Hassan; Ahlam Inayatullah Badrul Munir; M. Husaini A. Rahman (World Academy of Science, Engineering and Technology, 2024)
Non-Indexed Publication